STRATEGI PENINGKATAN MINAT MENGHAFAL AL-QUR’AN SANTRI DI PONDOK PESANTREN AR-RAHMAH CURUP - Meirani Agustina; Ngadri Yusro; Syaiful Bahri (Didaktika : Jurnal Kependidikan, 2020)
Every Muslim believes that the Qur'an is the main source of Islamic teachings. The foregoing is a compulsory religious doctrine, and one cannot be called a good Muslim if he/she violates that belief. Thus, every Islamic educational institution must really make the Qur'an the main material which must be studied, and more specifically in the boarding school education. Reading or reciting, writing, memorizing, and making the Qur’an the life’s guidance are of the competencies that Muslim children must acquire. Hence, how is the interest of students from the Arrahmah Islamic Boarding School of Curup, Bengkulu, in memorizing the Qur'an? The foregoing became a major problem in this study whose answer had to be found by means of a qualitative approach. For the sake of garnering the accurate data, the researcher used interview and direct observation techniques conducted in the Arrahmah Islamic boarding school of Curup, Bengkulu. The present study revealed some internal and external factors influencing students’ interest in memorizing the Qur’an. Furthermore, the teachers’ efforts to increase students’ interest in memorizing the Qur’an fell into several ways: giving motivation, instilling habits to rehearse memorization/muraja'ah, maintaining good manners, increasing religious guidance activities, giving assignments, adding time allocation of learning, and improving the learning media and resources.Keywords: interest, memorizing the Qur’an, Islamic Boarding School students